Process of Indonesian Transnational Students to be Polyglots and Their Language Varieties in Japan - Aji Seno Suwondo; Waode Hamsia (JELITA, 2023)
This research was conducted to seek the process of Indonesian transnational students to be polyglots and what kind of speech varieties influenced them during that process in Japan. The present research conducted qualitative research with five Indonesian transnational students who settled in Japan for at least 1.5 years. Questionnaires and line phone call interviews were employed to collect data. Purposive sampling was applied to gain the subjects. The result found that four of the subjects reached an advanced level of Japanese language proficiency through numerous exposures, Japanese classes, watching television, and reading newspapers. Yet, a single subject remains at an intermediate level. Those exposures helped them to acquire Japanese and speech variety. Three of the subjects used the Kyoto dialect consciously since they got in touch with society and abandoned it when they moved to that another place. Yet the last two subjects did not use it. They only learned it because they had reasons that they were only students and would leave soon.